Optimisation and physicochemical characterisation of a thermo-alkali stable laccase produced by wastewater associated Bacillus sp. NU2 - Edoamodu, Chiedu E (Environmental technology, 2024)
Laccase is a multicopper enzyme that plays a unique role in bioremediation of environmental pollutants. Bacteria were isolated from hospital wastewater and screened for laccase production. The laccase production process condition was optimised, and the laccase obtained was characterised. The 16S rRNA molecular analysis conducted on the best laccase producer revealed a Bacillus sp. NU2 identified. The process conditions: pH5, 45°C, 100 rpm, 5% inoculum, and growth constituents viz: tangerine peel and wheat bran agro-wastes, beef extract, ammonium persulfate, glucose, galactose, xylose, sorbitol, fructose carbon sources; and 4-aminophenol inducer optimally stimulated laccase production. The Bacillus sp. NU2 laccase was optimal at pH and temperature conditions of 8.0°C and 60°C, with a noteworthy pH and thermal stability observed. Furthermore, NU2 laccase showed a moderate/high tolerance and relative activity effect on various chemical inhibitors, halides and surfactant of triton x-100 (105 ± 0.92%), PMSF (107 ± 0.81%), and NaCl (94 ± 0.81%) at 1, 3, and 6 (mM) concentration. Additionally, NU2 laccase maintained a relative activity of 101%, 104%, and 102% for Mg2+, Zn2+, and Fe3+ at 1, 3, and 6 mM respectively. Acetone and propanol significantly upregulated laccase activity at 114 ± 0.0008% and 118.24 ± 0.35 and also at 30 and 20 (%) concentrations. Conclusively, the tolerant effect of Bacillus sp. NU2 laccase in pH, temperature, inhibitors and organic solvents suggests its potential for biotechnological application and promotion of a greener environment